2020
DOI: 10.1002/ppul.25064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a long‐term exercise program on motor performance in children and adolescents with CF

Abstract: Objectives The aim of this study was to examine motor performance and trainability in youths with cystic fibrosis (CF). Methods Twenty‐two children and adolescents (11 f/11 m), age range 6–17 years (11.3 ± 3.3 years), mean FEV1 91.0 ± 21.7% pred.finished the partially monitored 12‐months exercise program. Patients performed the Deutsche Motorik Test (DMT) to assess flexibility, balance, strength, power and totalmotor performance. An incremental ergometer cycle test was used to assess maximal exercise capacity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
2
16
0
1
Order By: Relevance
“…The major findings of the present study were that the values of parameters of health-related fitness and motor performance-related fitness of children and adolescents with CF were lower than those of healthy controls of the same age. The present results confirm and extend the findings of previous studies that reported lower levels of health-related and motor performance-related fitness in youth with CF (Arikan et al., 2015; Corten & Morrow, 2020; Gruber et al., 2008, 2020). Additionally, this study highlighted that aspects of motor performance-related and health-related fitness linearly increased from middle to late childhood among youth with CF, whereas only minor changes or even a decline were observed among older adolescents.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The major findings of the present study were that the values of parameters of health-related fitness and motor performance-related fitness of children and adolescents with CF were lower than those of healthy controls of the same age. The present results confirm and extend the findings of previous studies that reported lower levels of health-related and motor performance-related fitness in youth with CF (Arikan et al., 2015; Corten & Morrow, 2020; Gruber et al., 2008, 2020). Additionally, this study highlighted that aspects of motor performance-related and health-related fitness linearly increased from middle to late childhood among youth with CF, whereas only minor changes or even a decline were observed among older adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…The exercise programs consisted of different sports activities with a great variety of demanding tasks. At the end of the exercise program, significant improvements in motor performance parameters were observed (Gruber et al., 2008, 2020). The authors concluded that activities highly demanding of motor skills had beneficial effects on neuromotor fitness, leading to corresponding adaptations in children and adolescents with CF (Stodden et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As seen in children with CF [20], our data suggest that there is trainability of adults with CF regarding their physical fitness. Due to a lack of studies, the importance of those parameters in context to CF remains unclear.…”
Section: Discussionsupporting
confidence: 61%
“…However, little is known about the effects of an exercise program regarding different aspects of motor performance fitness. In this respect, children and adolescents show trainability with regard to motor performance fitness as recently published by our group [20].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation